Economic implications of multiple births: inpatient hospital costs in the first 5 years of life. Issue 6 (21st October 2004) - Henderson, J; Hockley, C; Petrou, S; Goldacre, M; Davidson, L
Abstract : Objectives: To estimate long term health service costs for hospital stays associated with singleton, twin, and higher order multiple births up to 5 years of age. Design: Costs from specialty based data from the English Department of Health's NHS Trust Financial Returns were applied to admissions recorded in the Oxford record linkage study during 1970–1993. Setting: Oxfordshire and West Berkshire, United Kingdom. Subjects: A total of 276 897 children, of whom 270 428 were singletons, 6284 were twins, and 185 were higher order multiple births. Main outcome measures: Duration of hospital admissions during the first 5 years of life. Costs, expressed in £ sterling and valued at 1998–1999 prices, of hospital inpatient services. Results: The total duration of hospital admissions for twins and triplets were respectively twice and eight times that for singletons, once duration of life had been taken into account. Inpatient costs were significantly higher for multiple births than for singletons, with the cost differences concentrated in the first year of life. Over the first 5 years of life, the adjusted mean cost was estimated at £1532 (95% confidence interval (CI) £1516 to £1548) for singletons, £3826 (95%CI £3724 to £3929) for twins, and £8156 (95%CI £7559 to £8754) for higher order multiple births (p < 0.0001). Conclusions: Multiple births contribute disproportionately to hospital inpatient costs, especially during the children's first year of life.